EVALUATION OF THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN MATHEMATICS LEARNING AT SMA NEGERI 5 MEDAN CITY - Kinanti, Anggi Anastasia; Adlina, Zuraidah (Universitas Islam Sumatera Utara, 2024)
This study aims to evaluate the implementation of the Independent Curriculum in Mathematics learning at SMA Negeri 5 Medan City. Using a descriptive qualitative approach, data was collected through interviews, observations, questionnaires, and documentation studies. The subjects of the study include Mathematics teachers, students, principals, and parents of students. The results of the study show that teachers' understanding of the principles of the Independent Curriculum is quite good, but the implementation of project-based learning and technology integration still faces obstacles, especially limited facilities and preparation time. The majority of students feel that the learning methods in the Independent Curriculum are more interesting and relevant to real life, although some of them have difficulty adjusting. School management support has been provided through training and the provision of facilities, but budget constraints hinder the optimization of curriculum implementation. These findings support a theory of constructivism and active learning that emphasizes the importance of hands-on experience and student participation. The main recommendations are to increase teacher training, strengthen student guidance, and procure technology facilities. With these steps, it is hoped that the implementation of the Independent Curriculum can improve the quality of Mathematics learning as a whole. This research contributes to the development of the implementation strategy of the Independent Curriculum, especially in the subject of Mathematics.